Evaluation of Strategic Management Components in the Universities of Iran with Internationalization Approach - Gharavi, Behrooz (International Review of Management and Marketing, 2017)
Purpose: Evaluation of strategic management components in the universities of Iran is carried out by internationalization approach. This has a great importance in terms of health and survival of organization and codification and appropriate implementation of strategies. As managers and other stakeholder in codification process and strategy implementation are not aware of the effective factors of this process and reasons of failure in practice as well as they don't benefit from proposed theoretical frameworks, successful implementation of strategic management will be so difficult or sometimes impossible. Therefore, there is a need for accurate investigations about the key factors of codification and implementation of the most practical management tools. Thus, a comprehensive knowledge is acquired to help the policymakers consider effective implementation of strategic plans. Method of research: this is a descriptive research and analytical type. Statistic population of the research includes 800 faculty members of the universities of Tehran during2005-2006. Cochran sampling method was used and 260 people were selected as sample. Data have been analyzed and calculated by SPSS software. Results and conclusion: the obtained results have indicated that the strategic management components with internationalization approach are desirable. This can be accepted for management to consider possibilities, limitations and educational implications, exchange of information between managers and faculty members of universities, management control over implementation of educational strategies and the emergence of strategic implications. Keywords: strategic management, internationalization approach, Iran JEL Classification: L1